CAMPUS MARKETPLACE SEBAGAI INOVASI DISRUPTIF DI PERGURUAN TINGGI (STUDI PADA LSPR PLAZA) - Raden Adi Cahyadi; Yuliana Riana Prasetyawati (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2022)
The presence of e-commerce also supports increasing the entrepreneurial spirit and encourages the birth of young entrepreneurs in universities. This opportunity was captured by Bhinneka, which in 2020 made a new innovation by launching a collaboration and collaboration program between industry and universities in Indonesia to create a business ecosystem platform that is mutually beneficial for all stakeholders involved, both from the university and from the company. Disruptive innovation cannot be separated from the role of technology. The key is to find new, low-cost technologies that match innovation. This study uses a qualitative approach with a descriptive study. This study used the interview method for primary data collection. Interviews were conducted with internal sources from LSPR Plaza and external sources from Bhinneka who are partners of LSPR Plaza. Data analysis uses data reduction, data presentation, and drawing conclusions. The results show that disruptive innovation by presenting a campus marketplace not only builds an entrepreneurial spirit among the academic community, but also helps increase the market share of the assisted MSMEs.